ANALISIS PENGARUH LAYANAN SAMSAT WARUNG KOPI TERHADAP KEPUASAN MASYARAKAT KOTA LHOKSEMAWE - Chaidir, Chaidir; fairus, fairus; Sari, Riezky Purnama; Nabilla, Ulya; Nurviana, Nurviana; Amelia, Amelia; Fuad, Muhammad (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2023)
Samsat Warung Kopi is the newest innovation product from the Lhoksemawe Samsat Service in 2021 with the aim of making the vehicle tax payment process fast, easy and in a pleasant atmosphere for people who want to pay taxes. The aim of this research is to determine the quality of Samsat warung kopi’s services on the satisfacation of the people of lhokseumawe. The data used is primary data in the form of a questionnaire results distributed to 59 respondents. The results of the analysis show that Samsat Warung Kopi's services in paying vehicle tax is considered to be very good (81.09%). Community satisfaction with the quality of Samsat Warung Kopi's services in paying vehicle tax is rated as Very Good (83.67%). Regression Value Y = 17,222+ 0.893X. dan based on the results of the hypothesis test, it was concluded that that samsat warung kopi’s services had a very significant effect on community satisfaction. The percentage of influence of the coffee shop vehicle tax payment service on Lhokseumawe community satisfaction was 0.239 or 23.9% and the remainder was influenced by variables not included in this research.